Prarancangan Pabrik Asam Benzoat Dengan Proses Oksidasi Toluena Dan Katalis Kobalt Asetat Kapasitas 40.000 Ton/Tahun - Huda, Aimatul; , Ir. Herry Purnama, M.T., Ph.D; , Ir. Haryanto AR., M.S (2017)
Benzoic acid (C6H5COOH) is a chemical used as a food preservative, antiseptic, manufacture phenol etc. Benzoic acid is produced using toluene oxidation process which is carried out in a bubble reactor with cooling water and proceed on a liquid-gas phase. The reaction is exothermic with the operating conditions at a temperature of 150oC with pressure 3 atm. After reacting, materials and products are put into the next process, namely centrifugal decanter, distillation towers, crystallizer, filters, evaporator and rotary dryer. Purity of benzoic acid crystals is 99.5%. Benzoic acid plant requires raw materials, such as toluene at 3.793,35 kg/hour, O2 amounted to 4.036,22 kg/hour and a cobalt acetate catalyst of 9,63 kg/hour. Utilities included water supply is obtained from river water. Amount of make up water is used as much as 26.058,76 kg/hour. Demand of steam is 15.363,56 kg/hour, requirement of dowtherm A is 05.563,32 kg/h, amount of compressed air is 36,70 m3/hour, amount of electricity is 156,43 kW and amount of fuel is 325,56 m3. Benzoic acid plant is planned to stand in 2020 in the area of Tuban, East Java. Fixed capital investment (FCI) of this plant is Rp 200.325.790.440, and amount of working capital (WC) is Rp 15.001.223.509. The cost of annual production is Rp 146.479.005.291. From the economic analysis it can be shown that the Percent return on investment (ROI) before taxes is 28,48% and ROI after tax is 21,36%. Pay out time (POT) before tax is 2,60 years, while after tax is 3,19 years. Break even point (BEP) is 51,32%. The amount of shut down point (SDP) is 25,69%, and the discounted cash flow (DCF) is 32,43%. From the results of the economic analysis of benzoic acid plant with oxidation process is feasible to set up in Indonesia.